TRANSFORMING HEALTH IN TURKEY an evaluation of two decades of reform. - Başar, Dilek; Öztürk, Selcen (PRODUCTIVITY PRESS, 2025)
"Turkey's Health Transformation Programme (H.T.P.) has been instrumental in reshaping the country's healthcare landscape, aiming at enhancing accessibility, efficiency, and quality of services. Despite generating significant academic and policy interest, there remains a gap in consolidated scholarly resources. This forthcoming book addresses this need, synthesizing existing research to provide a comprehensive overview and critical analysis of the H.T.P.'s impacts from multiple perspectives. Structured into five main sections, the book delves into the H.T.P.'s policy changes, theoretical framework, and intended outcomes since its inception in 2003. It then assesses its effects through various lenses: from the government's strategic planning and economic considerations to healthcare providers' experiences and institutional dynamics, and finally, from the users' perspective, evaluating access, quality, and social implications. Additionally, a comparative analysis with similar reforms worldwide offers lessons and future directions. Targeting academics, healthcare professionals, policymakers, and students interested in health economics and policy analysis, this book aims to fill a critical gap in the literature, providing insights for ongoing and future reforms not only in Turkey but also in comparable global contexts"--